Participation tactics of elite freestyle wrestlers in competition system in 2013-2016 Olympic cycle - Zadorozhna, O. R.; Briskin, Y. A.; Pityn, M. P. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. Tactics is one of the basic terms underlying the management of competitive activities of athletes. In freestyle wrestling, the participation tactics of athletes in the competition system is covered fragmentally and needs proper justification. The purpose of the study was to determine the features of the participation tactics of elite athletes in the competition system in freestyle wrestling during 2013-2016 Olympic cycle. Materials and Methods. This study analyzes the dynamics of performances and results of 24 elite freestyle wrestlers who won gold, silver and bronze medals at the Games of XXXI Olympiad 2016 in Rio de Janeiro in different weight categories (four athletes in each of six weight categories). To do this, we used athletes` individual profiles on the United World Wrestling. Used an expert assessment devoted to the issues of tactics and tactical training. The experts (n = 8) were well educated (3 among them held Ph.D. diplomas) and experienced - 2 coaches of Ukrainian national team, and 1 athlete-national team`s member. On average, experts had almost 10 years of experience in training wrestlers of different ages. The results were processed using Microsoft Excel software. Results. The volume of competition practice of elite athletes during 2013-2016 changed in each season. In the 2013 season, the average group number of competitions in which athletes participated was 3.84 ± 2.06, in 2014 - 3.50 ± 1.79. In the 2015 season, those indicators were the highest - 4.17 ± 1.87, but in 2016 they decreased to 3.71 ± 1.52. The participation tactics in the competition system in freestyle wrestling during the season and the four-year cycle differed depending on the dynamics of sports results. Four types of tactics used by the elite athletes in freestyle wrestling in 2013-2016 were identified: leadership holding, gradual improving of results, combined, leadership returning. It was found that during 2013-2016, most athletes (58.33-79.17%) used a variety of tactics that involved performances in one Olympic weight category. In 2014 and 2015, some athletes (20.83 and 25.00%, respectively) used different options in other weight categories, choosing one of them as a priority and one or two - as additional. Conclusions. There are four types of participation tactics in the competition system in freestyle wrestling. In 2013-2016 Olympic cycle they included leadership holding, gradual increase of results, combined, leadership return. The main differences between types of tactics are the volume of competition practice, the dynamics of results, the choice of weight category. The most relevant was the type of tactics with performances exclusively in the Olympic weight category during four seasons.